EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN WORD SQUARE DENGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMP 9 PADANGSIDIMPUAN - SALMA RITONGA (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2019)
ABSTRACT The aims of this study is to describe the effectiveness of using word square learning model on students’ mathematical problem solving ability on the topic social arithmetic at the seventh grade student of SMP Negeri 9 Padangsidimpuan. This research was conducted by applying experimental (one group pre test post test design) with 23 students as the sample and they were taken by using random sampling technique from 168 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using word square learning model was 2.7 (good category) and b) the average of students’ mathematical problem solving ability on the topic social arithmetic before using word square learning model was 48.61 (fair category) and after using word square learning model was 80.865 (very good category). Furthermore, by using N-Gain formulation the result showed G=0.68 (middle effective), it means using word square learning model was effective on students’ mathematical problem solving ability on the topic social arithmetic at the eighth grade student of SMP Negeri 9 Padangsidimpuan. Keywords: effectiveness, word square, problem solving ability